Motives For Social Media Use (A Descriptive Study of Followers The Tiktok Account @Gerryanodv) - Trijayanto, Danang; Muhammad, Idrus (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
TikTok influencer @gerryanodv uses the TikTok social media platform to share fitness content and motivate followers. The problem formulation in this study is "What are the motives behind the media usage of followers of the TikTok account @gerryanodv?" The aim is to describe and analyze the motives of followers regarding the content presented by the TikTok account @gerryanodv. The research method employed is qualitative descriptive, with data collection techniques including interviews and documentation, involving 10 informants who have followed the TikTok account @gerryanodv for more than 6 months and have interacted with the content. The research results indicate that the TikTok account @gerryanodv presents various types of content to meet the diverse needs of the audience, ranging from information and entertainment to relaxation and health. The account successfully attracts attention and retains audience interest by offering content that aligns with their preferences and needs, particularly in the context of fitness and personal motivation.